(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The paper examines our understanding of climate change, and how it becomes a most dangerous threat to the humanity. We must understand what the science says, what we delivered, and what the economy demands. On 9th of August 2021, the intergovernmental panel on climate change (IPCC) released a report on climate change. The report states that the catastrophic impacts of rising climate risks will breach the 1.5˚c barrier within the next two decades and if emissions are not mitigated this made weather conditions more unpredictable or make them worse. In this paper we study the impacts with every increment of global warming on weather conditions, sea level rise and global surface temperature etc.